2002
DOI: 10.1159/000049367
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among the Indices of High-Resolution Computed Tomography, Pulmonary Function Tests, Pulmonary Perfusion Scans and Exercise Tolerance in Cases of Chronic Pulmonary Emphysema

Abstract: Background: Mismatched distribution of pulmonary blood flow is a common characteristic in emphysematous patients. But few reports have mentioned the relationships between the morphological changes in the lungs as assessed by high-resolution computed tomography (HRCT), pulmonary blood flow (PBF) scan and the indices of exercise tolerance. We investigated these relationships. Objective: Pulmonary function tests (PFT), HRCT, single photon emission computed tomography (99mSPECT) and treadmill exercise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…31,34,44,45 However, only a few studies examined the association of CT scan fi ndings with exercise tolerance. [14][15][16]18 Two reports studied only 20 subjects with COPD. 15,16 For example, Wakayama et al 16 found that emphysema score correlated significantly with 6MWD ( r 5 2 0.74).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,34,44,45 However, only a few studies examined the association of CT scan fi ndings with exercise tolerance. [14][15][16]18 Two reports studied only 20 subjects with COPD. 15,16 For example, Wakayama et al 16 found that emphysema score correlated significantly with 6MWD ( r 5 2 0.74).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16]18 Two reports studied only 20 subjects with COPD. 15,16 For example, Wakayama et al 16 found that emphysema score correlated significantly with 6MWD ( r 5 2 0.74). In a recent study of The dependent variable is 6-min walk distance, and the independent variables are FEV 1 % predicted, BMI, age, sex, race, % gas trapping, and the interaction of % gas trapping with FEV 1 % predicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this technique can provide information on the perfusion pattern in patients with severe emphysema, it suffers from low spatial resolution. SPECT has the potential for superior evaluation, but it is rarely used because the technique is very time-consuming and not widely available [7,8]. MRI appears to be a more promising technique owing to its high diagnostic accuracy in the detection of perfusion abnormalities and the ability to provide lobar and segmental analysis of perfusion defects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The expiratory D index was also closely correlated with K CO in our patients, although the extent of LAA on CT was not signifi cantly correlated. CT has certain limitations in detecting emphysematous lungs because of limited spatial resolution [22][23][24][25][26][27]. The earlier clinical studies showed a relatively low prevalence of LAA on CT, regardless of signifi cant airfl ow limitation in respiratory function test in PE patients [22,24].…”
Section: Discussionmentioning
confidence: 99%